Virtual reconstruction of the Australopithecus africanus pelvis Sts 65 with implications for obstetrics and locomotion. Issue 99 (October 2016) - Claxton, Alexander G.; Hammond, Ashley S.; Romano, Julia; Oleinik, Ekaterina; DeSilva, Jeremy M.
Abstract: Characterizing australopith pelvic morphology has been difficult in part because of limited fossilized pelvic material. Here, we reassess the morphology of an under-studied adult right ilium and pubis (Sts 65) from Member 4 of Sterkfontein, South Africa, and provide a hypothetical digital reconstruction of its overall pelvic morphology. The small size of the pelvis, presence of a preauricular sulcus, and shape of the sciatic notch allow us to agree with past interpretations that Sts 65 likely belonged to a female. The morphology of the iliac pillar, while not as substantial as in Homo, is more robust than in A.L. 288-1 and Sts 14. We created a reconstruction of the pelvis by digitally articulating the Sts 65 right ilium and a mirrored copy of the left ilium with the Sts 14 sacrum in Autodesk Maya. Points along the arcuate line were used to orient the ilia to the sacrum. This reconstruction of the Sts 65 pelvis looks much like a "classic" australopith pelvis, with laterally flared ilia and an inferiorly deflected pubis. An analysis of the obstetric dimensions from our reconstruction shows similarity to other australopiths, a likely transverse or oblique entrance of the neonatal cranium into the pelvic inlet, and a cephalopelvic ratio similar to that found in humans today.